Short-Circuit Fault Discrimination Using SiC JFET-Based Self-Powered Solid-State Circuit Breakers in a Residential DC Community Microgrid - Palaniappan, Karthik; Sedano, Willy; Vygoder, Mark; Hoeft, Nicholas; Cuzner, Robert; Shen, Z. John (IEEE transactions on industry applications, 2020)
This article identifies and validates the use of ultrafast silicon carbide (SiC) junction field effect transistor (JFET)-based self-powered solid-state circuit breakers (SSCBs) as the enabling protective device for a 340 Vdc residential dc community microgrid. These SSCBs will be incorporated into a radial distribution system in order to enhance fault discrimination through autonomous operation. Because of the nature and characteristics of short-circuit fault inception in dc microgrids, the time-current trip characteristics of protective devices must be several orders of magnitude faster than conventional circuit breakers. The proposed SSCBs detect short-circuit faults by sensing the sudden voltage rise between its two power terminals and draw power from the fault condition itself to turn off SiC JFETs and then, coordinate with no-load contacts that can isolate the fault. Depending upon the location of the SSCBs in the microgrid, either unidirectional or bidirectional implementations are incorporated. Cascaded SSCBs are tuned using a simple resistor change to enable fault discrimination between upstream high-current feeds and downstream lower current branches. Operation of one of the SSCBs and three in cascaded arrangements are validated both in simulation and with a hardware test platform. Thermal impact on the SSCB is discussed as well. The target application is a residential dc microgrid that will be installed as part of a revitalization effort of an inner city Milwaukee neighborhood.